Sustentatibilidade econômica de um S.A.E. (Serviço de Água e Esgoto) uma análise crítica - Bernardo, Carla Cristina (2009)
Water, which is needed by all living beings, is considered an economic and environmental possession of invaluable value to the life of the planet. It is found in Brazil as a possession of public domain, according to the Federal Constitution of 1988 and Law 11.445, of January 5 of 2007, which establishes the guidelines for the federal policy of sanitation. There is, therefore, the concept of ownership of management relevant to the State, with participation by the society. Wanting to demonstrate that it is possible to attain economic sustainability of a S.A.E, through the appropriate management, the case of the city of São José do Rio Preto will be studied, where the delivery of water supply and sanitation is done by a municipal authority created in August 21 of 2001, called SeMAE (Serviço Municipal Autônomo de Água e Esgoto). In the last decades it was verified, in a national territory level, trends for greater participation of private enterprises in the industry of sanitation, which contradicts the predominance, in most of the world, of public and local management. Referencing certain features of sanitation services, such as the essentiality and natural monopoly, there is a pressing need for social control. But the lacks of resources, ridiculous charges, practices of welfarism, and political interference, combined with poor management, have led to a scenario where the privatization appeared as salvation. With the introduction of National Sanitation Policy in 2007 and increased participation of the Federal Government, through the provision of programs and funding for the sector, an other reality is shown. The State, now defined as owner of sanitation services, walks in a path full of obligations and duties, in search of quality, efficiency and universal provision of the service. During the conception of this work, through the observation of the existing structures, institutional, physical, and operational of the Water and Sewer Service (W.S.S.) analysed, using data collected and carefully selected, were prepared initial diagnosis and procedures which corroborated with the evolution of this system. The comparative data used, coming mostly from the SNIS National Information of Sanitation System. The analysis and developmente of this work is permeated by the economic perspective. It avaliates, in the period from 2001 to 2008, the system of water supply and sewerage of São José do Rio Preto by means of measurable parameters and values, demonstrating its sustainability.